THEORY OF DIGNIFIED JUSTICE AS A LEGAL FOUNDATION OF LAW REFORM IN INDONESIA - Teguh Prasetyo; Tri Astuti Handayani (Surakarta Law and Society Journal, 2018)
Every country, and the nation builds its own legal theory in order to explain every legal phenomenon in each country. Similarly, the theory used to explain law reform. During this time, generally used Western theories to justify the model of law reform used throughout the world, including those who are aware or unaware of various Western legal theories that have been used in Indonesia, to understand, explain, justified law reform in Indonesia. Therefore, without intent to underestimate the efforts of scientists and philosophers in understanding the law, it is time for us to build our own theory. A theory of one's own that is more suitable for us in order to understand and explain the legal phenomena that are around us and that we experience ourselves. This short paper contains a description of the main points, concerning a new legal theory. This new theory, if it can be used in order to understand, explain or even justify the legal system based on Pancasila. This includes understanding and explaining law reform in Indonesia. The new theory, I call it the Theory of Dignified Justice. This theory was built in Indonesia with sources or references of legal (materials) in Indonesia. As a product of thinking activities the theory of dignity takes the process of thinking activities characterized as fundamental or radical thinking. Keywords: Dignified Justice, Law Reform, Pancasila Law.